ART SPACE: AN EXPERIMENTAL DIGITAL ART GAME - Gintere, Ieva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article examines the discourse concerning modern game theory and suggests a new method of research and knowledge transfer in the field of digital art game creation. The method is embodied in the new game Art Space that utilizes current research results in the field of contemporary aesthetics. Art Space is an experimental digital game that is being created in collaboration between researcher, Dr.art. Ieva Gintere (Vidzeme University of Applied Sciences, Latvia) and the game artist, Mag.art. Kristaps Biters (Liepāja University, Latvia) within the framework of a post-doctoral project. The concept of this new art game arises from the historical heritage of modern art. The aim of the game is knowledge transfer: the author has been carrying out research into contemporary digital games in order to transfer the results of the research to develop an appreciation and understanding of aesthetics in Art Game’s players. The game links aesthetics to art games by identifying modern trends such as pixel art, glitch, noise, and others. Due to the dearth of written information on the subject of modern art heritage in digital games, the study presents an innovative approach to art gaming explaining modern art’s cultural backgrounds. The methods used are audio-visual and stylistic analyses of games as well as studies of the existing literature. The project hopes to raise the interest of the wider public concerning contemporary art and music, point out the newest creative tendencies in art, and suggest potential changes in the language of art in the near future. This paper continues previously published research that helped to create the concept and design of Art Space, and focuses on the trends of photorealism and futurism.